Hbr's 10 must reads on managing people, vol. 2 - Review, Harvard Business (Gildan Audio, 2020)
Are you a good boss-or a great one? Get more of the management ideas you want, from the authors you trust, with HBR's 10 Must Reads on Managing People (Vol. 2). We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you master the innumerable challenges of being a manager. With insights from leading experts including Marcus Buckingham, Michael D. Watkins, and Linda Hill, this book will inspire you to: draw out your employees' signature strengths; support a culture of honesty and civility; cultivate better communication and deeper trust among global teams; give feedback that will help your people excel; hire, reward, and tolerate only fully formed adults; motivate your employees through small wins; and foster collaboration and break down silos across your company.
Downloadable audio file
Keywords: Business; Affaires; businesses (business enterprises); BUSINESS & ECONOMICS; Leadership; Downloadable audio books; Audiobooks; Livres audio